“PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA MAN 1 BENGKALIS” - Aliasir Fahmi; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstark: The problem in this study is that the Smash does not cross the net with a height of 2.55 meters and can easily be blocked by opponents. Likewise, when easily blocking, the opponents set up the ball without any obstacles. The title of this research is